PSYCHOLOGICAL RESILIENCE IN ADDRESSING JOB INSECURITY: THE MANIFESTATION OF SOCIAL SECURITY AMONG VULNERABLE WORKERS - Tutut Handayani; Randi Arfanda Reza (RADJA PUBLIKA, 2025)
This study aims to examine how psychological resilience influences risk perception and its implications for social security participation among informal sector workers. Using a Systematic Literature Review (SLR) method, 23 peer-reviewed articles from the Scopus database were analyzed to identify thematic patterns and research gaps. The findings indicate that while resilience and risk perception are rarely measured explicitly, both are implicitly reflected in the narratives of vulnerability, job insecurity, and survival strategies employed by informal workers. High resilience in informal workers often fosters an adaptive attitude towards uncertainty, but conversely, it can lower their perception of long-term risks that should ideally be anticipated through social security schemes. These findings suggest that decisions to join or opt out of social security are not only influenced by economic and structural factors but also by complex psychological dynamics. Therefore, future research needs to integrate a multidisciplinary approach to more comprehensively understand participation behavior.